Pengaruh Audit Tenure, Kepemilikan Manajerial Dan Kompensasi Bonus Terhadap Manajamen Laba (Pada Perusahaan Manufaktur Sektor Aneka Industri Yang Terdaftar Di Bursa Efek Indonesia - Bella Pratiwi; Yunina Yunina; Mursidah Mursidah; Indrayani Indrayani (Jurnal Visioner & Strategis, 2021)
This study aims to examine and analyze the Effect of Tenure Audit, Managerial Ownership and Bonus Compensation. The population used in this study are various industrial sector manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the 2013-2019 period. This study used purposive sampling method in taking the sample and obtained 105 samples. Based on the analysis that has been done, the research results show that audit tenure and managerial ownership have no effect on earnings management. Bonus compensation has an effect on earnings management.